Essence of intellect and logic in the farabian tradition - Doskozhanova, A. B.; Nurysheva, G Zh.; Tuleubekov, A. S. (ҚазҰУ хабаршысы. Философия, саясаттану және Мәдениеттану, 2015)
The article gives an analysis of that during the Islamic Middle Ages the Al-Farabi’s doctrine on intellect and logic took pride of place. The main point in this part of his philosophy is a belief in the power of human mind, as well as the human ability to discover the diversity of the world around owing to logic. Al-Farabi places no boundaries to human mind and his ability to penetrate into the essence of things. Value relevance of the Al- Farabi’s philosophical views is that it considers human reason, as coming from the Single Essence, as making human in form of consubstantial entities in God. Therefore, Al-Farabi fundamentally studied intellect. Intellect is a strict universality; following it means to be reasonable. Intellect acts as a universal principle of the formation of human personality and the cognitive process as a whole.